The Effects of Hormone Replacement Therapy (HRT) on Hemostatic Variables in Women with Previous Venous Thromboembolism – Results from a Randomized, Double-Blind, Clinical Trial - Høibraaten, Else; Qvigstad, Erik; Andersen, Trine Opstad; Mowinckel, Marie-Christine; Sandset, Per Morten (Thrombosis and Haemostasis, 2001)
In a recent randomized, double-blind, placebo-controlled trial of women with a history of venous thromboembolism (VTE), we found that hormone replacement therapy (HRT) was associated with an early excess risk of recurrent thrombosis. The aims of the present study were to characterize the effects of HRT on coagulation in these women to elucidate the mechanism(s) by which HRT increases the risk of thrombosis. The study comprised 140 women who were randomized to receive continuous treatment for 24 months with once daily 2 mg 17- -estradiol plus 1 mg norethisterone acetate (n = 71) or placebo (n = 69). HRT caused significant increases in prothrombin fragments 1+2, thrombin-antithrombin complex, and D-Dimer after 3 months, but these changes were less pronounced on prolonged treatment. The increases in markers of activated coagulation was higher in those women who subsequently developed recurrent thrombosis, but was similar in carriers and non-carriers of the factor V Leiden mutation. HRT had no effects on fibrinogen and factor VIII. Activated factor VII, but not factor VII antigen, decreased significantly on HRT as compared with placebo. The coagulation inhibitors antithrombin, protein C, and TFPI, but not protein S, all showed significant sustained decreases in the HRT group as compared with placebo. Antithrombin and protein C decreased by 8-12% on HRT, whereas TFPI activity decreased by 12-17% and TFPI free antigen by 29-30%. In multivariate analysis, only TFPI activity was a significant predictor for the increased activation of coagulation. We conclude that HRT was associated with early activation of coagulation, which corroborates the finding of an early risk of recurrent VTE. This activation may in part be explained by reduction in circulating anticoagulants.
Keywords: Hormone replacement therapy; venous thromboembolism; coagulation factors; coagulation inhibitors; activated coagulation